Potensi Karbon Pada Tegakan Hutan Adat Imbo Putui Desa Petapahan Kabupaten Kampar - Emy Sadjati; Joko Sulistyo; Azwin Azwin (Universitas Lancang Kuning, 2023)
Abstract Forests are one of the natural resources that can absorb carbon dioxide in the atmosphere in the process of photosynthesis, carbon dioxide (CO2) in the atmosphere is bound and converted into a form of energy (sugar clusters) that is beneficial for life. Forests are able to reduce carbon emissions and store them in various compartments such as plants, litter, and soil organic matter. Plants as carbon storage causes the concentration of carbon dioxide in the atmosphere to decrease. This study aims to calculate the potential for carbon stored and absorbed in the form of CO2 in the Imbo Putui customary forest, Petapahan Village, Kampar District. The study used a systematic sampling method with random start by making plots measuring 20 m x 20 m for poles and trees and 50 cm x 50 cm for litter sampling, the number of plots was 63 with a distance between plots of 100 meters. The research results show that the potential value of carbon stored in the 251 h-1 Imbo Putui customary forest reaches748,406.70tons of CO2 that consists of a tree level of 745,008.16 tons pole level of 3117.42 tons and litter of 281.12 tones